A β-titanium alloy with extra high strain-hardening rate: Design and mechanical properties. (15th March 2016) - Brozek, C.; Sun, F.; Vermaut, P.; Millet, Y.; Lenain, A.; Embury, D.; Jacques, P.J.; Prima, F.
Abstract: In this paper, a new β-metastable titanium alloy, based on the Ti–Cr–Sn system, displaying both an extremely high work hardening rate and a uniform deformation larger than 0.35, was designed and successfully tested. The compositional design was guided through a stability mapping approach based on the "d-electron design method" and using an unexploited region of the Bo/Md map. Detailed analysis of deformation mechanisms shows combined transformation-induced plasticity (TRIP) and twinning-induced plasticity (TWIP) effects, resulting in a complex network of microstructural features and giving rise to marked kinematic hardening. Graphical abstract: